2007
DOI: 10.1029/2006jg000371
|View full text |Cite
|
Sign up to set email alerts
|

Recent changes in nitrate and dissolved organic carbon export from the upper Kuparuk River, North Slope, Alaska

Abstract: Export of nitrate and dissolved organic carbon (DOC) from the upper Kuparuk River between the late 1970s and early 2000s was evaluated using long‐term ecological research (LTER) data in combination with solute flux and catchment hydrology models. The USGS Load Estimator (LOADEST) was used to calculate June–August export from 1978 forward. LOADEST was then coupled with a catchment‐based land surface model (CLSM) to estimate total annual export from 1991 to 2001. Simulations using the LOADEST/CLSM combination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
112
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(119 citation statements)
references
References 75 publications
(89 reference statements)
5
112
2
Order By: Relevance
“…These are not significantly different (p = 5.01; ANCOVA) from slope and y-intercept values of ?14.1 and ?458 in 1980 (p \ 0.0001;Peterson et al 1986). These findings are consistent with the analysis of McClelland et al (2007), who showed that, although DOC export from the Kuparuk watershed decreased in the 1990s, this was largely attributable to lower spring discharge rather than a change in discharge-specific concentrations.…”
Section: Changes In C and N Flux In The Kuparuk Riversupporting
confidence: 82%
“…These are not significantly different (p = 5.01; ANCOVA) from slope and y-intercept values of ?14.1 and ?458 in 1980 (p \ 0.0001;Peterson et al 1986). These findings are consistent with the analysis of McClelland et al (2007), who showed that, although DOC export from the Kuparuk watershed decreased in the 1990s, this was largely attributable to lower spring discharge rather than a change in discharge-specific concentrations.…”
Section: Changes In C and N Flux In The Kuparuk Riversupporting
confidence: 82%
“…We interpret this change in DIC to be a result of an increased contribution of deeper groundwater, like those indicated by the detailed generic simulations of Frampton et al (2011) of permafrost thawing effects on flow and flow pathways under long-term climate change, rather than to changes in external inputs (e.g., Sjöberg et al, 2013). There is not a concomitant decrease in DOC as has been observed from several studies from other permafrost influenced watersheds (Striegl et al 2005;Walvoord and Striegl, 2007;McClelland et al, 2007). Such a decrease has been attributed to increase in hydrological residence time and microbial breakdown of DOC that would otherwise be released to streams (Striegl et al, 2005).…”
Section: The Role Of Shifting Flow Pathways For Dic and Doc Concentramentioning
confidence: 63%
“…Slumping of permafrost soils into Alaskan streams increases their inorganic and organic concentrations (Bowden et al, 2008), but phosphorus adsorption onto clays may decrease SRP concentrations in some mineral permafrost environments (Breton et al, 2009). Nitrate export from the Kuparuk River catchment on the Alaska North Slope increased 5-fold between the late 1970s and early 2000s and may have been related to permafrost soil and vegetation effects (McClelland et al, 2007). These processes may also operate in the peatland permafrost sites studied here.…”
Section: Nutrient Enrichmentmentioning
confidence: 81%